Graphene-Based Kinetic Promotion of Gas Hydrate Formation - Sun, Meng-Ting; Zhang, Guo-Dong; Wang, Fei (Frontiers in Chemistry, 2020)
Gas hydrate technology holds great potential in energy and environmental fields, and achieving efficient gas hydrate formation is critical for its industrial application. Graphene is a novel carbon-based nanostructured material with excellent thermal conductivity and a large specific surface area. Therefore, the use of graphene-based materials for the promotion of gas hydrate formation might be feasible and has aroused a lot of interests. Accordingly, to evaluate the current research on graphene-based promotion of gas hydrate formation, this work presents a review of existing studies involving graphene-based promoters of gas hydrate formation. Here, the studies applying various types of graphene-based promoters for gas hydrate formation are listed and detailed, the peculiar properties of graphene-based promoters are discussed, and the promotion mechanisms are analyzed. Through this review, comprehensive insight into graphene-based promotion of gas hydrate formation can be obtained, which can guide the design and applications of novel graphene-based promoters and might contribute to achieving efficient gas hydrate formation.